Preventive Medication Patterns in Bipolar Disorder and Their Relationship With Comorbid Substance Use Disorders in a Cross-National Observational Study - Icick, Romain; Melle, Ingrid; Etain, Bruno; Høegh, Margrethe Collier; Gard, Sébastien; Aminoff, Sofie R.; Leboyer, Marion; Andreassen, Ole A.; Belzeaux, Raoul; Henry, Chantal; Bjella, Thomas D.; Kahn, Jean-Pierre; et al. (Frontiers in Psychiatry, 2022)
Objective: The potential role of sub-optimal pharmacological treatment in the poorer outcomes observed in bipolar disorder (BD) with vs. without comorbid substance use disorders (SUDs) is not known. Thus, we investigated whether patients with BD and comorbid SUD had different medication regimens than those with BD alone, in samples from France and Norway, focusing on compliance with European guidelines. Methods: 770 patients from France and Norway with reliably ascertained BD I or II (68% BD-I) were included. Medication information was obtained from patients and hospital records, and preventive treatment was categorized according to compliance with guidelines. We used Bayesian and regression analyses to investigate associations between SUD comorbidity and medication. In the Norwegian subsample, we also investigated association with lack of medication. Results: Comorbid SUDs were as follows: current tobacco smoking, 26%, alcohol use disorder, AUD, 16%; cannabis use disorder, CUD, 10%; other SUDs, 5%. Preventive medication treatment was found non-compliant in 8% and partly compliant in 44% of the sample based on international guidelines. Treatment compliance was not different in BD with and without SUD comorbidity, as was supported by Bayesian analyses (highest Bayes Factor =0.16). Cross national differences in treatment regimens led us to conduct country-specific adjusted regression analyses, showing that (i) CUD was associated with increased antipsychotics use in France (OR =2.4, 95% CI =1.4-3.9, p =0.001), (ii) current tobacco smoking was associated with increased anti-epileptics use in Norway (OR =4.4, 95% CI =1.9-11, p <0.001) and (iii) AUD was associated with decreased likelihood of being medicated in Norway (OR =1.2, 95% CI =1.04-1.3, p =0.038). Conclusions: SUD comorbidity in BD was overall not associated with different pharmacological treatment in our sample, and not related to level of compliance with guidelines. We found country-specific associations between comorbid SUDs and specific medications that warrant further studies.